KOMUNIKASI INTERPESONAL PADA KORBAN BODY SHAMING TERHADAP TINGKAT KEPERCAYAAN DIRI DI KABUPATEN LANGKAT - Firda Yulia; Anang Anas Azhar (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to find out how interpersonal communication among victims of body shaming affects the level of self-confidence in Langkat district. The development of the era has not made humans stop criticizing or judging someone freely without thinking about other people's feelings, including the standardization of the ideal body, one of which is body shaming. Body shaming is the act of criticizing and commenting negatively on the body or body of another person. The researcher uses a qualitative approach that is more descriptive in nature and the data collected is in the form of words so that they are able to provide an overview of social and cultural phenomena in the community concerned. The characteristics of the informants in this study were women and men, aged 18-22 years, and never married. In Langkat district itself, body shaming is still common, both from one's own family, friends and other people. Words or actions that are raised make the level of self-confidence decrease. The interpersonal communication that was carried out succeeded in making the victim feel free and free from the responses given by those closest to them. The emotional feelings experienced by victims of body shaming such as sadness, anger, anger and even insecurity will be released if the victim tells what happened to the closest person in order to relieve discomfort and restore the victim's self-confidence.